2020
DOI: 10.1371/journal.pone.0229610
|View full text |Cite
|
Sign up to set email alerts
|

Two-step magnetic bead-based (2MBB) techniques for immunocapture of extracellular vesicles and quantification of microRNAs for cardiovascular diseases: A pilot study

Abstract: Extracellular vesicles (EVs) have attracted increasing attention because of their potential roles in various biological processes and medical applications. However, isolation of EVs is technically challenging mainly due to their small and heterogeneous size and contaminants that are often co-isolated. We have thus designed a two-step magnetic bead-based (2MBB) method for isolation a subset of EVs as well as their microRNAs from samples of a limited amount. The process involves utilizing magnetic beads coated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 46 publications
(53 reference statements)
2
20
0
Order By: Relevance
“…Diagram comparing EV‐CATCHER to 10 commercially available kits and ultracentrifugation for purification of small‐EVs. Three magnetic‐bead purification methods were identified where chemical treatment have been described (1% Formic Acid pH 2.0‐ 4.0, 0.1 M Glycine pH 2.5‐3.0 (Chen et al., 2020; Hisey et al., 2018; Hong et al., 2014), or proprietary buffer (SBI ExoFlow)) for small‐EV release (Barros et al., 2018; Burkova et al., 2019; Gutzeit et al., 2014; Hardin et al., 2018; Huang et al., 2018; Mallegol et al., 2007; Patel et al., 2019; Peterson et al., 2015; Theodoraki et al., 2018; Velandia‐Romero et al., 2020; ). b.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagram comparing EV‐CATCHER to 10 commercially available kits and ultracentrifugation for purification of small‐EVs. Three magnetic‐bead purification methods were identified where chemical treatment have been described (1% Formic Acid pH 2.0‐ 4.0, 0.1 M Glycine pH 2.5‐3.0 (Chen et al., 2020; Hisey et al., 2018; Hong et al., 2014), or proprietary buffer (SBI ExoFlow)) for small‐EV release (Barros et al., 2018; Burkova et al., 2019; Gutzeit et al., 2014; Hardin et al., 2018; Huang et al., 2018; Mallegol et al., 2007; Patel et al., 2019; Peterson et al., 2015; Theodoraki et al., 2018; Velandia‐Romero et al., 2020; ). b.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the exact neutralizing mechanism of Covid‐19 convalescent circulating small‐EVs requires further evaluation, our observation that small‐EVs isolated from high anti‐spike IgG titer sera possess anti‐SARS‐CoV‐2 neutralizing activity has important implications for enhancement of convalescent plasma therapy or design of novel therapies. It is important to note that recent studies have demonstrated that immuno‐purified small‐EVs can maintain their functional properties (cellular uptake, signalling) with the purifying antibody attached to their surface (Chen et al., 2020; Hardin et al., 2018; Hisey et al., 2018; Hong et al., 2014; Patel et al., 2019; Peterson et al., 2015; Theodoraki et al., 2018; Velandia‐Romero et al., 2020). However, due to the possibility that some small‐EV functions may be compromised by antibody presence, for every new immuno‐purification protocol, it is necessary to initially evaluate their functionality by using small‐EVs purified by ultracentrifugation, as controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng et al [ 133 ] suggested that expression of miR-126 and miR-21 could be used for early detection of CVD, such as acute myocardial infarction and FH. Another study reported reduced plasma levels of EV-miR-126 in high-risk CVD patients and EV-miR-126 levels were negatively correlated with cardiac troponin I (cTnI) and N-terminal propeptide of B-type natriuretic peptide (NT-proBNP), suggesting miR-126 as a potential biomarker for CVD [ 103 ].…”
Section: Extracellular Vesicle As Biomarkers In Cvdmentioning
confidence: 99%
“…However, the relative abundance of cardiac secreted miRNAs within exosomes and/or other vesicles remains debatable. While Chen et al (2020) described higher plasma levels of miR-126 in the exosomal fraction compared to the non-exosomal fraction, another study suggests that plasmatic exosomal miRNAs are only a minority, with 90% of the plasmatic miRNAs being present in a non-membrane-bound form, possibly bound to a ribonucleoprotein complex ( Arroyo et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%